PENEGAKAN HUKUM SISTEM PERADILAN PIDANA DENGAN MENGGUNAKAN PENDEKATAN RESTORATIVE JUSTICE - Hendro Pally; Elfida Ratnawati Gultom (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Restorative justice or restorative justice implies, a rapprochement and redemption of mistakes that the perpetrators of criminal acts (families) want to do to victims with peace efforts outside the court with the intent and purpose that legal problems arising as a result of these criminal acts can be resolved properly, by reaching agreement and agreement between the parties. The expected goal of this research is to find the root causes of legal problems in the regulation of restorative justice law and the implementation of law enforcement in the criminal justice system in Indonesia. This study uses normative juridical research methods, using the Statute Approach approach based on legal norms and principles, applicable laws and regulations, legal theories and doctrines, jurisprudence, and other literature materials relevant to the topic study.